Program Pesantren Kilat Ramadhan untuk Meningkatkan Motivasi Ibadah Siswa SMPN 3 Tembilahan Hulu - Hendro Lisa; Mardiah Mardiah; Martina Napratilora (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The month of Ramadhan is the month of education (tarbiyah), which runs every year for a month. Ramadhan educates students to carry out fasting and practices that bring their advantages. The month of Ramadan is always awaiting by Muslims around the world. Ramadhan, its various functions and consequences, effected teachers' roles and responsibilities that must also deliver educating and guiding their students during the school day so that someday they become someone who can control their desires and have high motivation to do good deeds. The purpose of this community service was to increase students' motivation to worship through the Pesantren Kilat program. This activity was carried out at SMPN 3 Tembilahan Hulu, Indragiri Hilir, Riau, Indonesia. The pesantren kilat activities were important, to maintain the enthusiasm of student’s worship.